Amelioration of Dalton's lymphoma–induced angiogenesis by melatonin. Issue 6 (May 2017) - Kumari, Rani; Rawat, Kavita; Kumari, Anupma; Shrivastava, Anju
For tumor to grow beyond 1–2 mm 3 size, tumor recruits new blood vessels referred as angiogenesis; therefore, targeting angiogenesis can be a promising strategy to suppress cancer progression. In this study, in order to develop a good angiogenesis model, we investigated effect of Dalton's lymphoma on angiogenesis and further monitored the role of melatonin on regulation of angiogenesis. To evaluate angiogenesis, endothelial cells were isolated from main thoracic aorta and cultured in vitro in the presence or absence of Dalton's lymphoma supplemented with or without melatonin to monitor their role on its proliferation and migration, a hallmark of angiogenesis. Chick chorioallantoic membrane as well as mice mesentery which allows in vivo studies of tumor angiogenesis and testing of anti-angiogenic molecules was used to validate the in vitro analysis. To further extend our understanding about the regulation of the angiogenesis, we evaluated expression of tissue inhibitor of metalloproteinases 3, vascular endothelial growth factor, vascular endothelial growth factor receptor, and fibroblast growth factor in Dalton's lymphoma cells and mesentery by semiquantitative and quantitative reverse transcription polymerase chain reaction analysis. Dalton's lymphoma ascites induced significant increase in endothelial cell proliferation, migration, and sprouting of the tertiary branching in chorioallantoic membrane and mesentery of Dalton's lymphoma–bearing mice, whereas melatonin treatment led to their inhibition in a dose-dependent manner. Semiquantitative and quantitative reverse transcription polymerase chain reaction analysis of melatonin-treated Dalton's lymphoma cells and mesentery tissue clearly demonstrated restoration of angiogenesis-related genes tissue inhibitor of metalloproteinases 3 and reduction of vascular endothelial growth factor, vascular endothelial growth factor receptor, and fibroblast growth factor messenger RNA expression. Taken together, our results strongly demonstrate that Dalton's lymphoma provides pro-angiogenic environment leading to significant increase in angiogenesis, and further melatonin treatment reduced the Dalton's lymphoma ascites–induced angiogenesis implying that Dalton's lymphoma can serve as a very good model to study angiogenesis as well as for screening of drugs that can target angiogenesis.